2008
DOI: 10.3122/jabfm.2008.06.080042
|View full text |Cite
|
Sign up to set email alerts
|

Improving Chronic Kidney Disease Care in Primary Care Practices: An Upstate New York Practice-based Research Network (UNYNET) Study

Abstract: Background: With the prevalence of chronic kidney disease (CKD) in the United States rising from 10% to 13%, implementation of the evidence-based Kidney Disease Outcomes Quality Initiative guidelines, which were developed for the delay of progression of CKD, is of increasing importance in primary care offices. Previous studies have shown limited knowledge and uptake of Kidney Disease Outcomes Quality Initiative guidelines by primary care physicians. CKD and its complications are still largely under-diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 17 publications
0
58
0
2
Order By: Relevance
“…Southern California Kaiser Permanente developed an initiative to identify patients with CKD on the basis of KDOQI guidelines and alert PCPs, and found that nephrology visits increased modestly from 20% to 24% (42). The Upstate New York Practice-Based Research Network study examined computer decision-making support based on guidelines in primary care clinics and found that the recognition of CKD and diagnosis of anemia improved substantially (43). These two studies focused on improving recognition of CKD as opposed to addressing comprehensive CKD guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Southern California Kaiser Permanente developed an initiative to identify patients with CKD on the basis of KDOQI guidelines and alert PCPs, and found that nephrology visits increased modestly from 20% to 24% (42). The Upstate New York Practice-Based Research Network study examined computer decision-making support based on guidelines in primary care clinics and found that the recognition of CKD and diagnosis of anemia improved substantially (43). These two studies focused on improving recognition of CKD as opposed to addressing comprehensive CKD guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Other PBRNs have adopted this focus on quality improvement as well. 15 Elsewhere in the Journal, we present evidence suggesting that participation in PBRN studies can lead to long-term change in clinical practice behavior. 16 Although this work is preliminary, it raises intriguing questions about the potential for networks to create lasting change in the primary care clinical encounter, when they focus their research on topics of interest to the clinician and when they provide useful and feasible clinical tools to the clinician.…”
Section: Quality Improvement/clinical Practice Changementioning
confidence: 99%
“…12 We defined PCP recognition as documentation of a CKD diagnosis on the electronic problem list. [21][22][23] We defined the degree of nephrology involvement as (1) active co-management (nephrology visit within the prior 12 months), (2) past nephrology care (nephrology visit more than 12 months prior), or (3) no prior nephrology visits.…”
Section: Correlates Of Quality Of Carementioning
confidence: 99%